The reasonable supposition as opposed to the reasonable suspicion of committing a crime - Szymczyk, Andrzej (The Opole Studies in Administration and Law, 2017)
The article undertakes to describe the primary differences between the terms like the reasonable supposition of committing a crime, the reasonable suspicion of committing a crime and reasonable elements to the supposition of committing a crime, on the basis of the Polish law of criminal proceedings. The article discusses also the relation to language interpretation of the law, selected legal articles of the Code of Criminal Proceedings and undercover police work. Some examples of using the above-mentioned terms and the consequences related to them, as well as relations between them are pointed out as well.